Resin Monomers Act as Adjuvants in Ni-induced Allergic Dermatitis in vivo. (November 2014) - Bando, K.; Takahashi, H.; Kinbara, M.; Tanaka, Y.; Kuroishi, T.; Sasaki, K.; Takano-Yamamoto, T.; Sugawara, S.; Endo, Y.
Resin monomers (RMs) are inflammatory agents and are thought to cause allergic contact dermatitis (ACD). However, mouse models are lacking, possibly because of the weak antigenicities of RMs. We previously reported that inflammatory substances can promote the allergic dermatitis (AD) induced by intradermally injected nickel (Ni-AD) in mice. Here, we examined the effects of RMs on Ni-AD. To sensitize mice to Ni, a mixture containing non-toxic concentrations of NiCl2 and an RM [either methyl methacrylate (MMA) or 2-hydroxyethyl methacrylate (HEMA)] was injected intraperitoneally or into ear-pinnae intradermally. Ten days later, a mixture containing various concentrations of NiCl2 and/or an RM was intradermally injected into ear-pinnae, and ear-swelling was measured. In adoptive transfer experiments, spleen cells from sensitized mice were transferred intravenously into non-sensitized recipients, and 24 h later NiCl2 was challenged to ear-pinnae. Whether injected intraperitoneally or intradermally, RM plus NiCl2 mixtures were effective in sensitizing mice to Ni. AD-inducing Ni concentrations were greatly reduced in the presence of MMA or HEMA (at the sensitization step from 10 mM to 5 or 50 µM, respectively, and at the elicitation step from 10 µM to 10 or 100 nM, respectively). These effects of RMs were weaker in IL-1-knockout mice and in macrophage-depleted mice. Cell-transfer experiments in IL-1-knockout mice indicated that both the sensitization and elicitation steps depended on IL-1. Challenge with an RM alone did not induce allergic ear-swelling in mice given the same RM + NiCl2 10 days before the challenge. These results suggest that RMs act as adjuvants, not as antigens, to promote Ni-AD by reducing the AD-inducing concentration of Ni, and that IL-1 and macrophages are critically important for the adjuvant effects. We speculate that what were previously thought of as "RM-ACD" might include ACD caused by antigens other than RMs that have undergone promotion by the adjuvant effects of RMs.